SMRT sequencing revealed the diversity and characteristics of defective interfering RNAs in influenza A (H7N9) virus infection. Issue 1 (1st January 2019) - Lui, Wing-Yu; Yuen, Chun-Kit; Li, Can; Wong, Wan Man; Lui, Pak-Yin; Lin, Chi-Ho; Chan, Kwok-Hung; Zhao, Hanjun; Chen, Honglin; To, Kelvin K. W.; Zhang, Anna J. X; Yuen, Kwok-Yung; et al.
ABSTRACT: Influenza defective interfering (DI) particles are replication-incompetent viruses carrying large internal deletion in the genome. The loss of essential genetic information causes abortive viral replication, which can be rescued by co-infection with a helper virus that possesses an intact genome. Despite reports of DI particles present in seasonal influenza A H1N1 infections, their existence in human infections by the avian influenza A viruses, such as H7N9, has not been studied. Here we report the ubiquitous presence of DI-RNAs in nasopharyngeal aspirates of H7N9-infected patients. Single Molecule Real Time (SMRT) sequencing was first applied and long-read sequencing analysis showed that a variety of H7N9 DI-RNA species were present in the patient samples and human bronchial epithelial cells. In several abundantly expressed DI-RNA species, long overlapping sequences have been identified around at the breakpoint region and the other side of deleted region. Influenza DI-RNA is known as a defective viral RNA with single large internal deletion. Beneficial to the long-read property of SMRT sequencing, double and triple internal deletions were identified in half of the DI-RNA species. In addition, we examined the expression of DI-RNAs in mice infected with sublethal dose of H7N9 virus at different time points. Interestingly, DI-RNAs were abundantly expressed as early as day 2 post-infection. Taken together, we reveal the diversity and characteristics of DI-RNAs found in H7N9-infected patients, cells and animals. Further investigations on this overwhelming generation of DI-RNA may provide important insights into the understanding of H7N9 viral replication and pathogenesis.